COMPARISON OF PEAK GROUND ACCELERATION VALUES BASED ON DETERMINISTIC APPROACH USING EMPIRICAL EQUATIONS FOR THE CIMANDIRI FAULT: PERBANDINGAN NILAI PEAK GROUND ACCELERATION BERDASARKAN PENDEKATAN DETERMINISTIK PERSAMAAN EMPIRIS UNTUK SESAR CIMANDIRI - Haryanto; Setyo Budi, Agus; Setyo Rahman, Aditya; Dharma Persada, Yoga (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2025)
The Cimandiri Fault is often cited as the trigger for many large earthquakes in West Java. The Cimandiri Fault is a 100-km long active shear fault. This study aims to compare Peak Ground Acceleration (PGA) values generated by three empirical Ground Motion Prediction Equation (GMPE) equations, namely Boore (2003), Campbell (2003) and Chiou-Young et al. (2008), with a deterministic approach. The deterministic approach uses a simple formula that considers magnitude, distance and site conditions. The comparison results show that the PGA values predicted by the empirical equations of Boore, Campbell and Chiou Young are approximately the same, but there are several factors that differentiate the results of the three parameters. This indicates that the empirical equations consider more complex factors in predicting PGA, such as earthquake source mechanisms, geological structures and nonlinear effects. This study provides important information for understanding the distribution of PGA on the Cimnadiri fault. This information can be used to strengthen buildings and infrastructure in the future, thereby minimizing the risk of earthquake damage.